(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: This study is designed to study factors associated with tuberculosis in marshlands of Iraq Method: This is a case control study conducted in three governorates containing marshlands in the south of Iraq. Cases were new pulmonary TB case aged over 14 years and Control were age, sex and district matched other than TB patients seeking for health care in primary health care centers. Analysis used the following tests: Chi-square, T-test and Mann-Whitney tests. Findings: The study sample composed of 455 new TB cases and 444 controls. Males constituted 47% of both study groups. Mean age was 41.1±17.4 year for TB cases and 40.4±14.3 year for control group. Underweight was found more among TB cases (19% in cases and 6.9% in control group) (P< 0.05). Employment rate in cases was half that of control and housewives were more among cases (43.4% in cases and 28.2% among control) (P< 0.05). Duration of smoking was significantly longer in TB cases (18.6±13.7 year) than in control group (12.8±9.6 year) (P < 0.05). Diabetes rate was significantly higher among cases (16.6%) than in control (10.2%) (P< 0.05). Length of Dexamethasone use was significantly higher in TB patients (P< 0.05). It was significant to find TB cases more to have rooms without windows. Family size was higher in cases (P < 0.05) Conclusion: Main factors associated with TB in south of Iraq were underweight, unemployment, period of smoking, diabetes, period of Dexamethasone use, living in rooms devoid of windows and large family size. Poverty related factors are likely behind having TB in marshlands.